1984
DOI: 10.1159/000124038
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Peripeduncular Nucleus in the Neuroendocrine Control of Sexual Behavior and Milk Ejection in the Rat

Abstract: Electrocoagulations situated in the lateral midbrain tegmentum cause severe deficits in sexual behavior and lactational performance of rats. In this study we determined the extent to which these effects could be reproduced by axon-sparing lesions using the excitotoxin, ibotenic acid; in another group of rats, 6-OHDA was infused in the same area to degenerate the mesencephalic catecholamine neuronal elements affected by the electrocoagulations. It was found that ibotenic acid, but not 6-OHDA, reproduced most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 32 publications
2
40
0
Order By: Relevance
“…Subsequently, it was shown that neurober of intromissions preceding ejaculation as well as the length of time between intromissions (Emery chemical lesions at this same level reduce the ability of a male to ejaculate but not the ability to mount and Sachs, 1976;Valcourt and Sachs, 1979). These findings suggest that neurons activated within or intromit (Hansen and Kohler, 1984), suggesting that cells within this area are important for ejaculacMePD and specific subregions of BNSTpm during mating may be involved in the temporal sequencing tion, while fibers that traversed the area are important for mounting and intromitting. More reof male copulation.…”
Section: Copulatory Processesmentioning
confidence: 84%
“…Subsequently, it was shown that neurober of intromissions preceding ejaculation as well as the length of time between intromissions (Emery chemical lesions at this same level reduce the ability of a male to ejaculate but not the ability to mount and Sachs, 1976;Valcourt and Sachs, 1979). These findings suggest that neurons activated within or intromit (Hansen and Kohler, 1984), suggesting that cells within this area are important for ejaculacMePD and specific subregions of BNSTpm during mating may be involved in the temporal sequencing tion, while fibers that traversed the area are important for mounting and intromitting. More reof male copulation.…”
Section: Copulatory Processesmentioning
confidence: 84%
“…Neurophysiological inputs from suckling necessary for both neuroendocrine secretions controlled by the hypothalamus and kyphosis are transmitted in the spinal dorsolateral columns (Fukuoka et al, 1984;DuBois-Dauphin et al, 1985a;. This information diverges before or within the midbrain, because lesions of the PP nucleus disrupt suckling-induced oxytocin release but not kyphosis (Hansen and Köhler, 1984;DuBoisDauphin et al, 1985b;Hansen and Ferreira, 1986a;Factor et al, 1993). The spinomesencephalic tract transmits impulses from dorsal horn lamina I through the ascending dorsolateral columns of the spinal cord to synapse onto the cPAG l,vl , particularly at intercollicular levels (Swett et al, 1985;Yezierski, 1988), thereby possibly transmitting afferents from suckling as well as other somatosensory stimuli (Yezierski and Schwartz, 1986).…”
Section: Role Of the Cpag In Kyphosismentioning
confidence: 99%
“…With respect to maternal aggression in lactating rats, three excitatory regions have been identified: PP nucleus and two of its projection sites, amygdala and ventromedial hypothalamus (Hansen and Ferreira, 1986b;Hansen, 1989;Factor et al, 1993). Furthermore, maternal aggression in rats may require ventral trunk stimulation for its maintenance, because it is greatly reduced by lesions of the PP, part of the ascending milkejection pathway (Hansen and Köhler, 1984;Hansen and Ferreira, 1986a), by several hours of separation from the litter, or by anesthetization of the nipples and surrounding tissue (Stern and Kolunie, 1993). Hence, our finding that a small lesion in the cPAG, one that disrupts a SK-induced behavioral alteration (kyphosis), heightens maternal aggression was unexpected.…”
Section: Maternal Aggression and The Pagmentioning
confidence: 99%
“…Furthermore, they showed that unilateral lesion of this area prevents the response to contralateral suckling, but not ipsilateral suckling. It has also been suggested that the Field of Forel and zona incerta might predominantly mediate transmission of the suckling stimulus from the midbrain to hypothalamic oxytocin neurons [7]. However, a retrograde tracing study by Tribollet et al [8] showed that neurons in these areas are not labeled following injection of tracer into the SON, which suggests the existence of further relay sites that transmit the suckling stimulus information to the OT cells.…”
mentioning
confidence: 99%